A South Africa perspective: the modern company and corporate governance in the companies act, 2008 - Hajat, Humayra (My University, 2019)
This research report outlines the legal transformation of South African company law from its largely English colonial influence to its current form under the Companies Act 71 of 2008 (the 2008 Act). A most significant transformation has been the express inclusion of corporate governance in section 7(b)(iii) of the 2008 Act, and the further recognition that the companies cannot be divorced from its broader society. It is argued that practising good corporate governance, via stakeholder inclusivity, would allow for the company to become more lucrative and sustainable in the long-term. This research report advocates for the enlightened shareholder-value approach whereby directors will be able to ensure profit-making and accountability to their shareholders, whilst also protecting their investors, customer-base, reputation and credibility. The fiduciary duty for directors to act in the best interests of the company under section 76(3)(b) of the 2008 Act is interpreted as acting in the interests of the collective body of shareholders both in the short-term and in the long-term (a shareholder-centric approach). However, section 7 of the 2008 Act; the mandatory requirement of a social and ethics committee for public companies in the 2008 Act; the King reports (specifically King IV); and the pressing demands of the modern company indicate that directors are encouraged to consider concerns beyond just those of the shareholders for the ultimate betterment of the company. Of course, stakeholder inclusivity must be exercise in a reasonable and legitimate manner so as not to undermine profit maximisation and the overall best interests of the company.
Submitted in partial fulfilment of the requirements for the degree of Master of laws by coursework and research report at the University of the Witwatersrand, Johannesburg